1964
DOI: 10.1126/science.146.3645.762
|View full text |Cite
|
Sign up to set email alerts
|

Air Concentrations of Twelve Radionuclides from 1962 through Mid-1964

Abstract: New spectrometric techniques for the multidimensional counting of gamma rays permit the direct measurement of twelve radionuclides collected on air filters. Observed concentrations of Be(7), Na(22), Mn(54), Co(60), Y(88), Zr(95)-Nb(25), Ru(166), Sb(124), Sb(125), Cs(134), Cs(137), and Ce(144) during the past 2(1/2) years help to explain the origin and fallout rates of the trace radionuclides in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1965
1965
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The fallout of radionuclides peaked around 1964, and at this time ~°Co possibly occurred in fin whale livers, though in trace amounts. In fact, at that time s°Co and 6sZn were detected in the atmosphere (Perkins et al, 1964) and in various marine organisms apart from whales (Folsom and Young, 1965). It seems likely that the trace 8°Co peaks were overshadowed by the more prominent SsZn peak and the trace quantities of s°Co could not he detected by the counting techniques used in the 1960's.…”
Section: Resultsmentioning
confidence: 97%
“…The fallout of radionuclides peaked around 1964, and at this time ~°Co possibly occurred in fin whale livers, though in trace amounts. In fact, at that time s°Co and 6sZn were detected in the atmosphere (Perkins et al, 1964) and in various marine organisms apart from whales (Folsom and Young, 1965). It seems likely that the trace 8°Co peaks were overshadowed by the more prominent SsZn peak and the trace quantities of s°Co could not he detected by the counting techniques used in the 1960's.…”
Section: Resultsmentioning
confidence: 97%
“…If large quantities of earth are incorporated into the fireball, resulting fallout particles may contain large amounts of silicates which are relatively insoluble. On the other hand, detonations high in the atmosphere usually produce very small particles from which much of the radioactivity can be leached with water (Perkins, Thomas, and Nielsen, 1965). Neel and Larson (1963) found that solubility and consequently potential biological availability of 90 Sr in fallout increased with distance from ground zero.…”
Section: Fission Productmentioning
confidence: 98%
“…In addition to dating of various materials using 3 H or 14 C, some of the nuclides have been used as atmospheric tracers (Perkins and Nielsen, 1965). A number of the radionuclides listed in Table 1, including 3 H, 14 C, 7 Be, 22 Na,and 32 Pcanalso be produced by nuclear explosions.…”
Section: Natural Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Zn 65 and CoGO occur in atmospheric fallout (5), comparisons of the abundance of these two nuclides relative to fission products (such as Zr l :l: L Nb 95 ) in the sediment (4) indicate that from 1962 through mid-1964 (6) fallout was a smaller source of Zn G5 and COBO than the Columbia River was.…”
mentioning
confidence: 99%